Pragmatic analysis of age-related idioms in Abdulla Qodiriy’s “O‘tgan kunlar” - Omonova Nozigul Hamdam qizi (Euro Asian Journal Publishing, 2024)
This study provides a pragmatic analysis of age-related idioms in Abdulla Qodiriy’s O‘tgan kunlar, the first novel in Uzbek literature. Through examining seven idioms, including umr bermoq (to give life) and yoshga kirmoq (to come of age), the research highlights how language conveys societal values, generational dynamics, and social hierarchies. The idioms reflect cultural attitudes toward aging, maturity, and respect, serving as linguistic tools that manage interpersonal relationships and illustrate the complexities of Uzbek society. By applying theories of speech acts, and politeness, the study reveals how these idioms function beyond their literal meanings to mediate power relations and express social norms. This research fills a gap in Uzbek linguistic literature by advancing understanding of the role idioms play in constructing and negotiating generational roles
Keywords: Pragmatic analysis; age-related idioms; Uzbek literature